1998
DOI: 10.3928/1081-597x-19980901-17
|View full text |Cite
|
Sign up to set email alerts
|

Central Focal Interface Opacity After Laser in situ Keratomileusis

Abstract: BACKGROUND: The acute onset of a focal central interface opacity with visual loss following LASIK has not been described in the peer reviewed literature. Non-peer reviewed reports of various inflammatory lesions have been recorded. METHODS: We describe three cases in which an acute focal stromal interface opacification was identified within 1 week of laser in situ keratomileusis (LASDX). Each case was performed by a different surgeon on a different day, but using the same method, materials, and the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…This corneal opacity and hyperopic shift characteristically persist for 2-18 months before resolving spontaneously. [5,10,11] In our patient's 1st-week follow-up, we observed that the prognosis improved by the opacification in the center decreased and the visual acuity level increased to 0.9. After about 1.5 months, we determined that the pathology had improved significantly, both in imaging methods and in our biomicroscopic examination with a visual acuity level of 1.0.…”
Section: Accepted Manuscriptmentioning
confidence: 49%
See 2 more Smart Citations
“…This corneal opacity and hyperopic shift characteristically persist for 2-18 months before resolving spontaneously. [5,10,11] In our patient's 1st-week follow-up, we observed that the prognosis improved by the opacification in the center decreased and the visual acuity level increased to 0.9. After about 1.5 months, we determined that the pathology had improved significantly, both in imaging methods and in our biomicroscopic examination with a visual acuity level of 1.0.…”
Section: Accepted Manuscriptmentioning
confidence: 49%
“…Although the cornea is transparent on the 1st day after surgery, central corneal opacification in CTK begins with an appearance similar to DLK on the 1st or 2nd postoperative day and rapidly causes intense opacification of the central corneal stroma. This corneal opacity and hyperopic shift characteristically persist for 2 – 18 months before resolving spontaneously 5 , 10 , 11 . In our patientʼs 1st-week follow-up, we observed that the prognosis improved as the opacification in the center decreased and the visual acuity level increased to 0.9.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…CTK is initially described as a rare complication after LASIK surgery, mainly occurring within 9 days after refractive surgery, and patients may experience blurred vision, pain, photophobia, floaters, and foreign body sensation [ 27 , 28 , 29 ]. CTK presents as a central or peri-central amorphous corneal opacity with corneal striation, stroma thinning, and hyperopia shift.…”
Section: Discussionmentioning
confidence: 99%
“… 2 3 CTK was initially described in a case series after mechanical microkeratome-assisted laser in situ keratomileusis (LASIK) in 1998. 4 The incidence of CTK is rare and estimated to be 0.016% after refractive surgeries. 1 3 Several case studies claimed that the incidence of CTK is not exclusive to the mechanical microkeratome-assisted LASIK surgeries and has also developed after femtosecond LASIK, photorefractive keratectomy (PRK), trans-PRK, and small incision lenticule extraction surgeries.…”
Section: Introductionmentioning
confidence: 99%